Pyrroloquinoline quinone extends Caenorhabditis elegans' longevity through the insulin/IGF1 signaling pathway-mediated activation of autophagy. Issue 22 (14th October 2021) - Yang, Liu; Ye, Qi; Zhang, Xuguang; Li, Ke; Liang, Xiaoshan; Wang, Meng; Shi, Linran; Luo, Suhui; Zhang, Qiang; Zhang, Xumei
Abstract : Activation of autophagy involves PQQ-induced longevity effects. Abstract : Aging is the leading cause of human morbidity and death worldwide. Pyrroloquinoline quinone (PQQ) is a water-soluble vitamin-like compound that has strong anti-oxidant capacity. Beneficial effects of PQQ on lifespan have been discovered in the model organism Caenorhabditis elegans ( C. elegans ), yet the underlying mechanisms remain unclear. In the current study, we hypothesized that the longevity-extending effect of PQQ may be linked to autophagy and insulin/IGF1 signaling (IIS) in C. elegans. Our data demonstrate that PQQ at a concentration of 1 mM maximally extended the mean life of C. elegans by 33.1%. PQQ increased locomotion and anti-stress ability, and reduced fat accumulation and reactive oxygen species (ROS) levels. There was no significant lifespan extension in PQQ-treated daf-16, daf-2, and bec-1 mutants, suggesting that these IIS- and autophagy-related genes may mediate the anti-aging effects of the PQQ. Furthermore, PQQ raised mRNA expression and the nuclear localization of the pivotal transcription factor daf-16, and then activated its downstream targets sod-3, clt-1, and hsp16.2 . Enhanced activity of the autophagy pathway was also observed in PQQ-fed C. elegans, as evidenced by increased expression of the key autophagy genes including lgg-1, and bec-1, and also by an increase in the GFP::LGG-1 puncta. Inactivation of the IIS pathway-related genes daf-2 or daf-16 by RNAi partially blocked the increase in autophagy activity caused by PQQ treatment, suggesting that autophagy may be regulated by IIS. This study demonstrates that anti-aging properties of PQQ, in the C. elegans model, may be mediated via the IIS pathway and autophagy.